Die Gegenwart des Vergangenen im urbanen Raum Czernowitz-Innsbruck - Scharr, Kut; Barth-Scalmani, Gunda (innsbruck university press, 2019)
The cultural heritage of any society is mainly present in urban public space and in a variety of ways. The awareness and maintenance of this heritage in remembrance, however, is subject to continuously renewed contextualisation. In part this is due to changes in the social and political environment, but also to society handling its past in ongoing discursive process. Moreover, in the decades since the fall of the Iron Curtain in 1989, older structures have come to the fore, some have been forgotten or suppressed, new ones added. The city is generally seen as the entirety of a condensed human existence, with the urban public space, and how it is shaped over time, as inscriptions in the city's archive or memory. How this "archive" is accessed and understood depends on the opportunities for a methodological scientific toolkit and, most of all, on recognising, documenting and using the existing heritage. Taking advantage of a generously sponsored project of the Austrian agency for international mobility and cooperation in education and research, OeAD, a young generation of students from the universities of Chernivtsi (Ukraine) and Innsbruck (Austria) were able to familiarise themselves over two years with the multifaceted stored memory that is public space. They enjoyed academic support from faculty and representatives of selected museums in Tyrol and the Chernivtsi region. In the course of interdisciplinary exchange, the students took up exchange placements that taught them basic approaches to handling this important and sensitive social resource and to develop an intuition for it. The students also learned in practical terms how to carry a project through, from its inception via fieldwork in situ to the sometimes arduous task of writing it up and preparing texts for publication. There was also room for social aspects like solidarity, mutual support and maybe even friendship, especially between the young participants. These are among the most significant results of this undertaking. - Das kulturelle Erbe einer Gesellschaft ist vor allem im öffentlichen urbanen Raum in vielfacher Weise im Alltag präsent. Die Wahrnehmung und Pflege dieses Erbes in der Erinnerung ist indes einer ständigen Neukontextualisierung unterworfen. Gründe dafür liegen u.a. im veränderten gesellschaftlichen wie politischen Umfeld, aber auch im konstant diskursiven Umgang der jeweiligen Gesellschaft mit ihrer Vergangenheit. In den Jahrzehnten seit dem Fall des Eisernen Vorhangs 1989 haben sich zudem ältere Strukturen in den Vordergrund geschoben, Manches wurde vergessen oder verdrängt, Neues ist hinzugekommen. Gilt die Stadt gemeinhin als Grundgesamtheit eines verdichteten menschlichen Daseins, so sind der urbane öffentliche Raum und seine zeitlichen Prägungen Einschreibungen in ihr Archiv bzw. ihre Erinnerung. Zugriff und Verständnis dieses ,Archives' sind dabei abhängig von den Möglichkeiten eines methodisch wissenschaftlichen Instrumentariums, vor allem aber auch vom Erkennen, Dokumentieren und Nutzen des vorhandenen Erbes. Auf Basis eines vom Österreichischen Austauschdienst großzügig geförderten Projektes konnte sich über einen Zeitraum von zwei Jahren eine junge Generation von Studierenden der Universitäten Tscherniwzi (Ukraine) und Innsbruck (Österreich) unter wissenschaftlicher Begleitung sowie Vertretern ausgewählter Museen aus dem Bundesland Tirol und dem Gebiet Tscherniwzi mit dem facettenreichen Gedächtnisspeicher urbaner Raum vertraut machen. Im interdisziplinären Austausch gelang es, in Form eines wechselseitigen Praktikums grundlegende Ansätze zum Umgang mit und dem Gefühl für diese ebenso wichtige wie sensible gesellschaftliche Ressource zu vermitteln. Für die Studierenden bot das Vorhaben zudem die Möglichkeit, praxisnah ein Projekt von seinen Anfängen über die Feldforschung vor Ort bis hin zum nicht immer ganz mühelosen Schreiben der Texte sowie ihrer Publikationsvorbereitung zu gestalten. Solidarität, Kollegialität und vielleicht auch Freundschaft vor allem unter den jungen Menschen kamen dabei als soziale Aspekte keineswegs zu kurz. Sie zählen wahrscheinlich zu den wichtigsten Ergebnissen dieses Unterfangens.